MANAGEMENT OF INTERCULTURAL COMMUNICATION IN THE DEVELOPMENT OF INTERNATIONAL ECONOMIC RELATIONS: TRENDS AND TOOLS - AKSYONOVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to issues of intercultural communication in the context of the development of international economic relations. The purpose of the study is to explore aspects of intercultural communication and justify its managerial tools in the context of international economic relations.The article defines that effective interaction between representatives of different cultures is a key factor for successful business operations, decision-making, and conflict minimization in the global environment. The research analyzes the formation of intercultural communication as a scientific discipline, with a detailed examination of the contribution of defining high-context and low-context cultures. The characteristics of these cultural types are presented, explaining differences in communication styles, negotiation processes, and decision-making in international business.The study substantiates the relevance of applying the cultural dimensions’ model to analyze intercultural differences in international business. It identifies that dimensions such as power distance, individualism versus collectivism, masculinity versus femininity, uncertainty avoidance, long-term versus short-term orientation, and indulgence versus restraint determine the business behavior of representatives from different countries and influence the effectiveness of international interactions.The article argues that intercultural adaptation is a prerequisite for the successful functioning of companies in the global space, particularly by considering social, cognitive, and behavioral aspects of integration. The key barriers to intercultural communication that affect the effectiveness of international economic relations are identified, including language difficulties, sociocultural stereotypes, differences in management styles, ethical discrepancies, and inconsistencies in business etiquette.It is justified that overcoming these barriers is possible through the implementation of modern managerial tools, such as corporate training programs for the development of intercultural competence, digitalization of communication processes, and the use of artificial intelligence technologies to enhance intercultural communication.Overall, the study demonstrates that in today's globalized world, adapting management strategies to the cultural characteristics of the international environment is a necessary condition for increasing the competitiveness of international companies and ensuring their effective operations in the field of international business.
Keywords: intercultural communication; cultural differences; international economic relations; managerial tools; intercultural adaptation; digitalization; development of intercultural communication